SOCIAL PARTNERSHIP IN THE FIELD OF PRESERVATION OF HISTORICAL AND CULTURAL HERITAGE - Dmitry V. Kataev; Maxim V. Zubkov (Russian Studies in Culture and Society)
The article analyzes the trends and features of mutual relations between state authorities, civil society institutions, and the local population in the field of protection and popularization of cultural heritage objects in Russia as a source of social and cultural identification of society and the basis for the formation of spiritual and moral values.